355 Growth Performance of Neonatal Holstein Heifer Calves fed Milk Containing Essential oil Blend and/or Encapsulated Butyrate. (21st September 2022) - Liu, Ting; Zhihao, Luo; Li, Peng; Wu, Jianping; Casper, David P
Abstract: Previous research demonstrated the growth promoting benefits of an essential oil/oligosaccharide blend (EO; Stay Strong, Ralco, Inc.) or an encapsulated sodium butyrate (C4; Ultramix GF, Adisseo, Inc.) fed to neonatal calves. The possibility exists the technologies are additive based on individual mechanisms of action. The objective was to evaluate EO and C4 alone or combined when fed to Holstein heifer calves raised on a commercial Chinese dairy operation. Sixty-four heifers were blocked by calving day and randomly assigned to 1 of 4 treatments (N=16/treatment) using a randomized complete block design. Treatments were: 1) Control: CN; milk fed 3x/d; 2) EO added to the milk at the rate of 1.50 g/d; 3) C4 added to the milk at 1.70 g/d; and 4) EO&C4: EO and C4 added to the milk at the rates of 1.5 and 1.70 g/d, respectively. Calves were fed whole milk using an increasing/decreasing feeding program with weaning on d 60 and a 70-d experiment. Calf birth body weight (BW) was found to be a significant (P < 0.01) covariate with calves fed EO, C4, and EO&C4 demonstrating greater (P < 0.05) BW (41.9, 47.0, 46.6, and 48.0 kg for CN, EO, C4, and EO&C4, respectively) gains and average daily gains (602.0, 670.5, 665.7, and 683.7 g/d). compared with calves fed CN. Calf starter intake was greater (P < 0.05) for calves fed C4 compared with calves fed CN with calves fed EO and EO&C4 being intermediate and similar (P > 0.10). Calves fed EO and C4 demonstrated greater (P < 0.05) total blood serum volatile fatty acid concentrations (9.75, 12.91, 11.22, 10.89 µM) compared with calves fed CN with calves fed EO&C4 being intermediate and similar (P > 0.10). Calves fed EO, C4, and EO&CN demonstrated greater growth performance, but the combination did not further improve growth performance.